Sonographic and Endoscopic Findings in Cocaine-Induced Ischemic Colitis. (21st December 2015) - Leth, Thomas; Wilkens, Rune; Bonderup, Ole K.
Abstract : Cocaine-induced ischemic colitis is a recognized entity. The diagnosis is based on clinical and endoscopic findings. However, diagnostic imaging is helpful in the evaluation of abdominal symptoms and prior studies have suggested specific sonographic findings in ischemic colitis. We report sonographic and endoscopic images along with abdominal computed tomography in a case of cocaine-induced ischemic colitis.